Three-Dimensional Analysis of the Curvature of the Femoral Canal in 426 Chinese Femurs. (28th October 2015) - Su, Xiu-Yun; Zhao, Zhe; Zhao, Jing-Xin; Zhang, Li-Cheng; Long, An-Hua; Zhang, Li-Hai; Tang, Pei-Fu
Abstract : Purpose . The human femur has long been considered to have an anatomical anterior curvature in the sagittal plane. We established a new method to evaluate the femoral curvature in three-dimensional (3D) space and reveal its influencing factors in Chinese population. Methods . 3D models of 426 femurs and the medullary canal were constructed using Mimics software. We standardized the positions of all femurs using 3ds Max software. After measuring the anatomical parameters, including the radius of femoral curvature (RFC) and banking angle, of the femurs using the established femur-specific coordinate system, we analyzed and determined the relationships between the anatomical parameters of the femur and the general characteristics of the population. Results . Pearson's correlation analyses showed that there were positive correlations between the RFC and height (r = 0.339, p < 0.001 ) and the femoral length and RFC (r = 0.369, p < 0.001 ) and a negative correlation between the femoral length and banking angle (r = - 0.223, p < 0.001 ). Stepwise linear regression analyses showed that the most relevant factors for the RFC and banking angle were the femoral length and gender, respectively. Conclusions . This study concluded that the banking angle of the femur was significantly larger in female than in male.